Radiomodifying effects of RAPTA C and CDDP on DNA strand break induction. (December 2017) - Reimitz, Dan; Davídková, Marie; Mestek, Oto; Pinkas, Jiří; Kočišek, Jaroslav
Abstract: Experimental study is exploring combined effect of RAPTA C (Ru( η 6 -p-cymene)Cl2 (1, 3, 5-triaza-7-phosphatricyclo-[3.3.1.1]decanephosphine)) or CDDP (cis-diamminedichloridoplatinum(II)) and radiation on the DNA damage. When irradiating plasmid DNA in solution with free molecules, no combined effect is observed, indicating that the contribution to DNA damage caused by products of radiolysis of RAPTA C or CDDP is negligible in comparison to the damage caused by products of radiolysis of water. After binding to DNA, CDDP adducts with DNA strongly enhance the damage in a good agreement with the results of previous studies. RAPTA C adducts act radio-protective at low doses of OH radical scavenger - tris(hydroxymethyl)aminomethane (tris) and show no combined effects at higher tris levels. Radioprotectivity of RAPTA C is therefore primarily caused by enhanced resistance of RAPTA C modified DNA against the damage induced by radicals. Abstract : Highlights: Free RAPTA C or CDDP do not modify the radiation damage to DNA. Cisplatin adducts sensitize DNA to strand break formation. RAPTA C adducts protect DNA against strand break formation. RAPTA C selectively protects DNA against free OH radical attack.